TB or not TB? Definitive determination of species within the Mycobacterium tuberculosis complex in unprocessed sputum from adults with presumed multidrug‐resistant tuberculosis. Issue 9 (24th June 2021) - Mbelele, Peter M.; Sauli, Elingarami; Mpolya, Emmanuel A.; Mohamed, Sagal Y.; Addo, Kennedy K.; Mfinanga, Sayoki G.; Heysell, Scott K.; Mpagama, Stellah
Abstract: Objectives: Differences among Mycobacterium tuberculosis complex (MTC) species may predict drug resistance or treatment success. Thus, we optimised and deployed the genotype MTBC assay (gMTBC) to identify MTC to the species level, and then performed comparative genotypic drug‐susceptibility testing to anti‐tuberculosis drugs from direct sputum of patients with presumed multidrug‐resistant tuberculosis (MDR‐TB) by the MTBDRplus/sl reference method. Methods: Patients with positive Xpert ® MTB/RIF (Xpert) results were consented to provide early‐morning‐sputum for testing by the gMTBC and the reference MTBDRplus/sl. Chi‐square or Fisher's exact test compared proportions. Modified Poisson regression modelled detection of MTC by gMTBC. Results: Among 73 patients, 53 (73%) were male and had a mean age of 43 (95% CI; 40–45) years. In total, 34 (47%), 36 (49%) and 38 (55%) had positive gMTBC, culture and MTBDR respectively. Forty patients (55%) had low quantity MTC by Xpert, including 31 (78%) with a negative culture. gMTBC was more likely to be positive in patients with chest cavity 4.18 (1.31–13.32, P  = 0.016), high‐quantity MTC by Xpert 3.03 (1.35–6.82, P  = 0.007) and sputum smear positivity 1.93 (1.19–3.14, P  = 0.008). The accuracy of gMTBC in detecting MTC was 95% (95% CI; 86–98; κ = 0.89) compared to MTBDRplus/sl. All M. tuberculosis/canettii identified by gMTB were susceptible to fluoroquinolone and aminoglycosides/capreomycin. Conclusions: The concordance between the gMTBC assay and MTBDRplus/sl in detecting MTC was high but lagged behind the yield of Xpert MTB/RIF. All M. tuberculosis/canettii were susceptible to fluoroquinolones, a core drug in MDR‐TB treatment regimens.